Project 2A: Motif & pattern / Anis Zulfah Zulkifli - Zulkifli, Anis Zulfah (Perpustakaan Tun Abdul Razak, UiTM Sarawak, 2024)
The poster above is derived from analyzing the compositions of element sand design principles of Orang Ulu’s House. Orang Ulu’s house is known for it being elevated from the ground, supported by its massive columns. The columns are carved with motifs.